2011
DOI: 10.1007/s10530-011-0112-x
|View full text |Cite
|
Sign up to set email alerts
|

Plant community dynamics relative to the changing distribution of a highly invasive species, Eichhornia crassipes: a remote sensing perspective

Abstract: Eradicating or controlling invasive alien species has frequently had unintended consequences, such as proliferation of other invasive species or loss of ecosystem function. We explore this problem using a case study of a highly invasive floating aquatic macrophyte, water hyacinth (Eichhornia crassipes), in the Sacramento-San Joaquin Delta of California. We used 5 years of remote sensing data to perform change detection analysis to study plant community dynamics contemporaneous with changes in water hyacinth co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 37 publications
2
50
1
Order By: Relevance
“…It basically states that unused resources (the resource dimension of niche space) in a community make the community susceptible to invasion from a species that can exploit those resources. Although not an explicit test of empty niche hypothesis, Khanna et al (2012) found that E. crassipes and submersed aquatic macrophyte dynamics were opposite which indicated it was colonizing available ''empty'' space. They noted that even when submersed vegetation growth was pronounced, E. crassipes only colonized new sites, but in general did not show much growth when submersed vegetation was topped out.…”
Section: Empty Nichementioning
confidence: 89%
“…It basically states that unused resources (the resource dimension of niche space) in a community make the community susceptible to invasion from a species that can exploit those resources. Although not an explicit test of empty niche hypothesis, Khanna et al (2012) found that E. crassipes and submersed aquatic macrophyte dynamics were opposite which indicated it was colonizing available ''empty'' space. They noted that even when submersed vegetation growth was pronounced, E. crassipes only colonized new sites, but in general did not show much growth when submersed vegetation was topped out.…”
Section: Empty Nichementioning
confidence: 89%
“…has been documented in Liberty Island at least since 2004 but has increased in area since then (Khanna et al. ). The emergent marsh forms triangular shapes into the water that are separated by the original agricultural access roads between fields, with deposition starting along this edge and filling outward.…”
Section: Methodsmentioning
confidence: 99%
“…), and dynamic floating communities (Khanna et al. ). Water primrose has been mapped in this area since the 2000s and surged after the population crash of pennywort ( Hydrocotyle umbellata ) in the past decade (personal observation).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations